Case Report: Fournier's gangrene in children: a report of three cases from a pediatric center in Vietnam - Le, Hung Thanh; Nguyen, Dao Thi Anh; Vo, Trong Le Duc; Nguyen, Linh Thi Truc; Huynh, Chan Cong; Tran, Phu Dai; Ho, Cuong Trung; Nguyen, Quynh Tran Minh; Nguyen, An Tai (Frontiers in Pediatrics, 2026)
Fournier's gangrene (FG) is a form of necrotizing fasciitis affecting the perineal and external genital regions. It is a rare urological emergency, particularly uncommon in children. Accurate diagnosis, early administration of broad-spectrum antibiotics, and timely surgical debridement are essential for effective management. In this study, we present three distinct pediatric cases of FG. The first case involved a 10-month-old boy with no underlying health conditions who was successfully treated with favorable outcomes. The second case was a 12-year-old boy with dengue fever and extensive scrotal gangrene, who recovered well after a challenging postoperative course. The third case was a 4-year-old boy who developed necrotizing scrotal infection following a second-stage hypospadias repair. All three patients were promptly diagnosed and managed with early intervention.